Anxiety, Stress and Burnout among Nurses Involved in Covid 19 Duties in Cochin City, India - Pritpal Singh, Jithin Gangadharan K (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Aim: To conclude the level of anxiety, stress, and burnout amid the Nurses tangled in COVID 19 duties. Design: A cross-sectional revision was accompanied from Feb 15, 2021, to March 15, 2021. Methods: Google forms were distributed to all the Nurses involved in COVID 19 duties of Central, State, and Private hospitals of Cochin City. A simple random sampling method was used. 150 samples were selected and administered, The Corona Disease Anxiety Scale, The COVID stress scale, and Copenhagen Burnout Inventory. The reliability of the tool was found to be high, as it is a highly standardized internationally accepted tool. The data was analyzed using Z test and ANOVA and SPSS software. Results: 20.7% of Nurses have Very Low Stress, 20.7% have High Stress. 21.3% have Low Stress, 18.7% have Moderate Stress and 18.7% have Very High Stress. 52.7% of Nurses possess moderate anxiety levels. 25.3% have mild and 22% have severe anxiety.56.7% nurses possess a moderate level of burnout. 24.7% have mild burnout and 18.7% have severe burnout. Conclusion: There lies a major level of stress, anxiety, and burnout among Nurses that have to be addressed. Anxiety, stress, and burnout are positively correlated with each other.